2013
DOI: 10.3386/w19099
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclical Behavior of the Price-Cost Markup

Abstract: Wouters, and participants at numerous seminars for helpful comments. Ben Backes and Myungkyu Shim provided excellent research assistance. Valerie Ramey gratefully acknowledges financial support from National Science Foundation grant SES-0617219 through the National Bureau of Economic Research. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
166
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(190 citation statements)
references
References 119 publications
20
166
4
Order By: Relevance
“…While they study a dynamic setting with fixed prices under uncertainty, the model below is static and prices are always at monopolists' desired levels. A distinguishing feature of the shopkeeper setup is that markups are procyclical, consistent with the evidence in Nekarda and Ramey (2013).…”
Section: Introductionsupporting
confidence: 66%
“…While they study a dynamic setting with fixed prices under uncertainty, the model below is static and prices are always at monopolists' desired levels. A distinguishing feature of the shopkeeper setup is that markups are procyclical, consistent with the evidence in Nekarda and Ramey (2013).…”
Section: Introductionsupporting
confidence: 66%
“…Galí and Gertler, 1999) . Though, recent empirical estimates by Nekarda and Ramey (2010) suggest that markups might actually be procyclical. 12 The absence of capital goods in the economy means that, in equilibrium, output, , equals the level of consumption of the representative household, .…”
Section: Householdsmentioning
confidence: 99%
“…Other studies have focused on the inverse of the labor share, as this can be shown to be theoretically proportional to the markup if the production function is Cobb-Douglas. Nekarda and Ramey (2013) show that an upward trend of the markup began in the early 1980s. The rise in the markup coincides with the more aggressive role of monetary policy in stabilizing inflation.…”
Section: Empirical Motivation For Welfare Channelsmentioning
confidence: 99%